2017
DOI: 10.1111/jphd.12206
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality: caries‐related emergency department visits and follow‐up among children

Abstract: These National Quality Forum endorsed measures provide valid methodologies for assessing the rate of caries-related ED visits, an important system-level outcome indicator of outpatient prevention and disease management, and the timeliness of follow-up with a dentist. There is significant variation in caries-related ED visits among state Medicaid programs, and most ED visits do not have follow-up with a dentist within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Looking at the overall scores, the scores ranged from 38 to 78 out of 80 possible points. The highest scoring publications stem from the last 3 years . Appendix shows an oversight of the funding bodies and possible competing interests of the reviewed publications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Looking at the overall scores, the scores ranged from 38 to 78 out of 80 possible points. The highest scoring publications stem from the last 3 years . Appendix shows an oversight of the funding bodies and possible competing interests of the reviewed publications.…”
Section: Resultsmentioning
confidence: 99%
“…To guide decisions about which of the currently available measures to use to assess quality of oral health care, the authors recommend the measures from those publications that scored highest on the development, testing and validation of the measures. At this moment, the Dental Quality Alliance (DQA), Hummel et al, Bhardwaj et al and Neumann et al, showed the most extensive procedure to develop and/or test the quality measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic illnesses have been targeted in the PED, including screening, brief interventions and referrals [Chandler et al, 2015;Haber et al, 2015;Herndon et al, 2017;Vaughn et al, 2012]. Adolescents and low-income children who use PEDs have been shown to have unhealthy dietary behaviors and often do not obtain primary medical or preventive dental care [Chandler et al, 2015;Wall et al, 2014].…”
Section: Discussionmentioning
confidence: 99%